Design and implementation a single phase bi-directional DC-DC converter - Chulan, Megat Azahari (2007)
High frequency bi-directional dc-dc converters are currently widely used in a diversity of power electronic applications. In order to interconnect the various DC sources at different voltage levels, one requires bi-directional DC/DC converters capable of converting the voltage from one level to another whilst also able to control the direction of power flow through the converter. The use of a bi-directional dc-dc converter in motor drives devoted to Electric Vehicles (EV) allows a suitable control of both motoring and regenerative braking operations. A bi-directional arrangement of the converter is needed for the reversal of the power flow, in order to recover the vehicle kinetic energy in the battery by means of motor drive regenerative braking operations. A full-bridge, single phase inverter and converter that uses Pulse Width Modulation (PWM) to control the power switches was constructed. The concept of PWM with different strategies for converter is described. The PWM was produced with a simple circuit and using several chips and devices that are easily available in the market. The PWM signals are simulated using OrCAD simulation tools. MOSFET IRF520 is used for high frequency switching in both sides inverter and converter. An isolation transformer (ratio 1:1) is used between inverter outputs and input of bi-directional of DC-DC converter. The proposed converter has the advantages of high switching frequency, high efficiency, simple circuit, low cost and bi-directional power flow. The detailed design and operating principles are analyzed and described. The simulation and experimental waveforms for the proposed converter are shown to verify its feasibility.